Psychosocial factors in people with chronic kidney disease prior to renal replacement therapy. Issue 9 (26th August 2013) - McKercher, Charlotte; Sanderson, Kristy; Jose, Matthew D
Abstract: Increasing evidence implicates psychosocial factors including depression, anxiety, perceived social support and health‐related quality of life in the pathophysiology of various chronic diseases. Research examining the psychosocial aspects of kidney disease has focussed predominantly on depressive disorders in dialysis patients where they are independently associated with increased risk of mortality and poor health‐related quality of life. In contrast, studies examining the influence of psychosocial factors in people with chronic kidney disease (CKD) prior to the initiation of renal replacement therapy are sparse. Limited data indicate that clinical depression and depressive symptoms are common and may independently predict progression to dialysis, hospitalization and death. In contrast, the influence of anxiety disorders, lower perceived social support and impaired health‐related quality of life on the clinical course of CKD have received little attention. Large‐scale prospective cohort studies are needed to clarify the burden and prognostic impact of these factors in this vulnerable population. Given the escalating burden of CKD worldwide examining the role of these potentially modifiable risk factors is crucial. Identifying and implementing targeted interventions in order to prevent or delay the progression of CKD and improve quality of life will be a major challenge. Summary at a Glance: This review examines the burden and prognostic role of depression, anxiety, perceived social support and health‐related quality of life in adults with chronic kidney disease prior to renal replacement therapy. Further studies are required to clarify the relative influence of these factors on the disease trajectory of this population. Given the escalating economic and social burden of chronic kidney disease examining the role of potentially modifiable non‐biological risk factors is crucial.